Brain Shaped by Music Performance: Cognitive Effects and Genetic Approaches - Emel Güneş; Şayeste Çağıl İnal (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Music is a complex product of the brain, which contains various components such as pitch, rhythm, timbre, and due to this, it has always been an attractive subject for neuroscientists. With the increasing developments in imaging techniques, a variety of anatomical structures and functions associated with music has been found. Specifically, studies done with musicians revealed the changing brain areas with music performance as well as the affected cognitive functions due to near and far transfer. Cognitive functions such as verbal memory, motor functions, visual and spatial functions, executive functions are some of the cognitive components which are improved with music performance. Studies done with children who take musical training and musicians who started their training at an early age points to the fact that music performance results with brain plasticity and due to this fact, musician brain is appropriate to use as a plasticity model. Despite all these information, studies on molecular background of music has started quite recently and became a new research topic. Studies like twin studies, familial aggregation studies, genome wide association studies points out that musical abilities and behaviors could be based on genetics, along with suggesting several candidate genes. It is mostly known that these genes play important roles in brain, such as neural connections and conduction of neurotransmitters. All these results are fairly new and require in depth research.